THE POLITICAL ASPECT OF IMPLEMENTING UNCONDITIONAL INCOME IN THE STATE OF ALASKA (USA) - Kulyk, Vitalii (Public Management and Policy, 2025)
The article explores the political aspect of implementing an unconditional basic income in the state of Alaska (USA) through the lens of the Alaska Permanent Fund Dividend (PFD) program, which has been providing annual payments to residents from oil revenues since 1982. The study aims to analyze the historical preconditions of the PFD’s establishment, its impact on political activity and electoral behavior, and the contemporary political controversies and budgetary dilemmas that shape its sustainability in the 21st century. The research employs a comprehensive approach, integrating historical analysis, comparative methods, content analysis of official documents, scholarly works, and news reports, as well as correlation analysis of statistical data on payments, voter turnout, and budget indicators. The historical review reveals that the PFD emerged in 1976, driven by Governor Jay Hammond’s political vision and public consensus on the equitable distribution of oil revenues, securing its strong legitimacy. The analysis of political activity demonstrates that the PFD boosts voter turnout, particularly in years of high payments (e.g., 3,284 in 2022), though its role as a tool for populist mobilization remains debated. Current challenges stem from the program’s reliance on oil revenues and the tension between maintaining payouts and funding public services, intensifying political divisions and raising questions about its long-term viability amid economic and climate shifts. The findings highlight the dual nature of the PFD: it enhances democratic participation and public support while complicating budgetary planning. The article offers theoretical generalizations and practical insights valuable for the global discourse on unconditional income. The PFD stands as a unique case, illustrating both the benefits and limitations of such initiatives, emphasizing the need for adaptation to contemporary realities.